Review Of The Fund's Income Position For FY 2019 And FY 2020. (Policy Papers; Policy Paper ;, 2019)
This paper reviews the Fund's income position for FY 2019 and FY 2020. The paper updates projections provided in April 2018 and proposes decisions for the current year. The paper includes a comprehensive review of the Fund's income position as required under Rule I-6(4). No change is proposed in the margin for the rate of charge that was established under this rule in April 2018 for the period FY 2019-20.